Financial Literacy, Access to Digital Finance and Performance of Ugandan SMEs in Mbarara City - Bakashaba, Rennie; Musiita, Benjamin; Nabachwa, Sarah (Journal of Economics and Behavioral Studies, 2024)
This study investigates the relationship between financial literacy and access to digital finance, and how these impact the performance of small and medium-sized enterprises (SMEs) in Uganda. From a population of 4,776 SMEs in Mbarara City, the research uses a sample of 351 SMEs with a response rate of 99%, chosen based on the Krejcie and Morgan (1970) tables. To investigate the correlations between the variables, a cross-sectional design is used. The findings indicate a positive and significant relationship between financial literacy, access to digital finance and SME performance in Uganda. The regression analysis indicates that 45.7% of the variation in Ugandan SME performance can be explained by the combination of the effect of financial literacy and access to digital finance (adjusted R square = 0.457). This implies that the remaining 54.3% of the variation in SME performance was not taken into account in this study and is due to other factors. Given the significant amount of variation explained by these two variables, the study suggests that policymakers and stakeholders in Uganda’s SME sector prioritize programs aimed at enhancing SMEs’ financial literacy and access to digital finance. Additionally, the study recognizes the presence of other factors influencing SME performance, emphasizing the need for further research and attention in future planning.